Controle da coleção em microfilme Relatórios de presidentes de províncias, época do Imperio ([publisher not identified], 1980)
Index to the microfilm collection of "Relatórios" of the presidents of individual Brazilian states during the period of the Empire; filmed as part of a joint project of Biblioteca Nacional and Latin American Microfilm Project.